The Mental Health Predictors of Indonesian EPA Nurses and Certified Care Worker Candidates in Japan1. (11th November 2015) - Nugraha, Susiana; Ohara‐Hirano, Yuko
Abstract: This study was performed to identify predictors of the mental health of Indonesian nurse and certified care worker candidates who migrated to Japan under the Japan‐Indonesia Economic Partnership Agreement (EPA) 1 year after they migrated to Japan. A total of 92 people participated in this study. Twenty‐eight of the study participants were nurse candidates, and 64 of them were certified care worker candidates. Using the mental health status measured by the General Health Questionnaire (GHQ‐12) as the dependent variable, this cross‐sectional study aimed to identify the most appropriate model of mental health predictors for each occupation in the post‐migration stage using multiple linear regression analyses. The results showed that the mental health prediction model was different for the two occupational groups. Each predictor and the characteristics of the occupations will be discussed.